Variation in tuberculosis treatment outcomes and treatment supervision practices in Uganda. (December 2020) - Berger, Christopher A.; Kityamuwesi, Alex; Crowder, Rebecca; Lamunu, Maureen; Kunihira Tinka, Lynn; Ggita, Joseph; Sanyu Nakate, Agnes; Namale, Catherine; Oyuku, Denis; Chen, Katherine; Turyahabwe, Stavia; Cattamanchi, Adithya; et al.
Abstract: Background: Variation in healthcare delivery is increasingly recognized as an important metric of healthcare quality. Directly observed therapy (DOT) has been the standard of care for tuberculosis (TB) treatment supervision for decades based on World Health Organization (WHO) guidelines. However, variation in implementation of DOT and associated TB treatment supervision practices remains poorly defined. Methods: We collected individual patient data from TB treatment registers at 18 TB treatment units in Uganda including District Health Centers, District Hospitals, and Regional Referral Hospitals. We also administered a survey and did observations of TB treatment supervision practices by health workers at each site. We describe variation in TB treatment outcomes and TB treatment supervision practices. Results: Of 2767 patients treated for TB across the 18 clinical sites between January 1 and December 31, 2017, 1740 (62.9%) were men, most were of working age (median 35 years, interquartile range [IQR] 27 – 46), 2546 (92.0%) had a new TB diagnosis, and nearly half (45.9%, n = 1283) were HIV positive. The pooled treatment success proportion was 69.4% (95% confidence interval [CI] 67.8 – 71.1) but there was substantial variation across sites (range 42.6 – 87.6%, I-squared 92.7%, p < 0.001). The survey and observation of TB treatment practices revealed that the majority of sites practice community-based DOT (66.7%, n = 12) and request a family member, who receives no additional training or supervision, to serve as a treatment supporter (77.8%, n = 14). At TB medication refill visits, all sites screen for side effects and most assess adherence via self-report (83.3%, n = 15). Only 7 (38.9%) sites followed-up patients who missed appointments using either phone calls (22.2%, n = 4/7) or community health workers (16.7%, n = 3/7). All 18 sites counseled patients at treatment initiation, but none provided additional counseling at refill visits other than addressing poor adherence or missed appointments. Conclusion: There was substantial variation in implementation of DOT, including observation and documentation of daily dosing, training and supervision of treatment supporters, and follow-up for missed clinic visits. Identifying best practices and reducing uncontrolled variation in the delivery of TB treatment is critical to improving treatment outcomes.